KATALIS BIMETAL Cu-Cr/DIATOMEA UNTUK HIDROGENASI MINYAK SAWIT - Husni Husin (Agricultural Faculty, 2012)
A series of bimetallic Cu-Cr supported onto diatomite was synthesized using impregnation method and characterized using X-ray diffractometer (XRD) technique. The catalyst compositions were CuCrO2, Cu2O, Al2O3 and SiO2. The catalyst contained 5, 10, 20, and 30 wt.% of Cu-Cr respectively, with Cu : Cr ratio of 1:1. The catalytic performance of the samples was evaluated based on the application to a hydrogenated palm oil at 70oC and 7 bar of pressure by measuring its iodine number. The result showed that the bimetallic Cu-Cr deposited onto diatomite was an effective catalysts for hydrogenation of palm oils and its catalytic activity was highly dependent on the composition of metals. Iodine number of palm oil decreased to 27.2 from 43.28 by using of 30 wt.% of Cu-Cr after 120 minutes reaction almost similar to the performance of commercial nickel catalyst that could decrease the iodine number to 26.1. Keywords: hydrogenation, palm oil, copper-chromium, diatomite, impregnation.